Adolescent health programming in India: a rapid review - Alka Barua; Katherine Watson; Marina Plesons; Venkatraman Chandra-Mouli; Kiran Sharma (BMC, 2020)
Abstract Background Recognizing the potential of the country's large youth population and the importance of protecting and supporting its health and well-being, the Government of India committed to strengthening its programmes and systems for adolescents, initially through the Adolescent Reproductive and Sexual Health Strategy (ARSH) launched in 2005 and, subsequently, through the National Adolescent Health Programme (Rashtriya Kishore Swaasthya Karyakram or RKSK) launched in 2014. In 2016, in response to a request from the Government of India, the World Health Organisation undertook a rapid programme review of ARSH and RKSK at the national level and in four states (Haryana, Madhya Pradesh, Maharashtra and Uttarakhand) to identify and document lessons learnt in relation to four domains of the programmes (governance, implementation, monitoring and linkages) that could be used to enhance current and future adolescent health programming in India. Methodology and findings A rapid programme review methodology was utilised to gain an overview of the successes and challenges of the two adolescent health programmes. A desk review of policy statements, Program Implementation Plans (PIPs) (Program Implementation Plan (PIP) is an annual process of planning, approval and allocation of budgets of various programmes under the National Health Mission (NHM). It is also used for monitoring of physical and financial progress made against the approved activities and budget. ), reports and data provided by the four State governments was conducted alongside 70 semi-structured interviews with health, education and NGO officials at national, state, district and block levels. Data showed that the ARSH Strategy put adolescent health on the agenda for the first time in India, though insufficient human and financial resources were mobilised to ensure maximum impact. Further, the Strategy's focus on clinical service provision in a limited number of health facilities with a complementary focus on promoting community support and adolescent demand for them meant that services were not as easily accessible to adolescents in their communities, and in addition many were not even aware of them. Under RKSK, significant investment has been made in adequate management structures, as well as in community engagement and clinical service delivery at all levels of the health system. Monitoring the quality of service delivery remains a challenge in all four of the states, as does training of counsellors, nodal officers and other implementing partners. Additionally, further thought and action are required to ensure that peer educators are properly trained, supported and retained for the programme. Conclusions India's RKSK clearly integrated learning from the earlier ARSH Strategy. The findings of this review present an opportunity for the government and its partners to ensure that future investment in adolescent health programming continues to be framed around lessons learnt across India.